(untitled) (Research, Society and Development, 2025)
Objective: To analyze the contributions of nursing to promoting patient safety in individuals undergoing cardiac surgery, considering the context of public policies, care protocols, and educational practices. Methodology: This is an integrative literature review that used databases such as LILACS, BDENF, and SciELO, with a time frame from 2013 to 2025. Results: Six relevant studies were identified, addressing aspects such as postoperative nursing diagnoses, the use of clinical protocols, adverse events, knowledge of vasoactive drugs, and the importance of professional training and continuing education. The findings indicate that nursing plays a central role in strengthening the patient safety culture but faces structural challenges such as resource shortages, training gaps, and the lack of standardized practices. Final Considerations: It is concluded that the National Patient Safety Policy directly contributed to strengthening professional training, and adherence to evidence-based protocols is a key strategy for improving care quality.